2018
DOI: 10.1161/circresaha.118.312660
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Redox State and Efficiency of Glucose Oxidation With miR Based Suppression of Maladaptive NADPH-Dependent Malic Enzyme 1 Expression in Hypertrophied Hearts

Abstract: A maladaptive increase in anaplerosis via ME1 in TAC is associated with reduced GSH content. Suppressing increased ME1 expression in hypertrophied rat hearts, which is also elevated in failing human hearts, reduced pyruvate carboxylation thereby normalizing anaplerosis, restoring GSH content, and reducing lactate accumulation. Reducing ME1 induced favorable metabolic shifts for carbohydrate oxidation, improving intracellular redox state and enhanced cardiac performance in pathological hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…The capacity for FAO is reduced in the failing heart, setting the stage for a compensatory increase in glucose utilization, though increased glycolysis has been shown to outpace the increases in downstream pyruvate oxidation due to PDH inhibition and elevated pyruvate carboxylation via malic enzyme 1 (43). These collective fuel metabolic disturbances set the stage for a mitochondrial fuel (acetyl-CoA) input deficit.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity for FAO is reduced in the failing heart, setting the stage for a compensatory increase in glucose utilization, though increased glycolysis has been shown to outpace the increases in downstream pyruvate oxidation due to PDH inhibition and elevated pyruvate carboxylation via malic enzyme 1 (43). These collective fuel metabolic disturbances set the stage for a mitochondrial fuel (acetyl-CoA) input deficit.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation concerns the mechanisms underlying the effect of MCD inhibition on cardiac function. Emerging evidence has shown that downregulating malic enzyme 1 expression in failing hearts induces favorable shifts in not only improving coupling between glycolysis and glucose oxidation, but also improving redox state and contractile function (39). As MCD inhibition enhances the antioxidative capacity in MI hearts in conjunction with the improved uncoupling of glycolysis and glucose oxidation, whether this is achieved by preserving nicotinamide adenine dinucleotide phosphate through reducing malic enzyme 1 thereby mediating coupling of glycolysis and glucose oxidation, needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, though, that it remains unclear whether the increase in myocardial glucose oxidation rates is mechanistically required for how irbesartan attenuates diastolic dysfunction in response to angiotensin II infusion. Myocardial anaplerosis can also be targeted to attenuate cardiac dysfunction in response to TAC-induced pressure overload in male Sprague Dawley rats, as adenoviral delivery of a microRNA specific to malic enzyme improved contractile function during isolated Langendorff perfusions at 12 weeks post-TAC (Lahey et al, 2018). Taken together, it does appear that modifying myocardial energy metabolism can mitigate cardiac dysfunction in experimental models of cardiac hypertrophy.…”
Section: Energy Metabolism As a Target To Alleviate Cardiomyopathymentioning
confidence: 96%